Turbidity removal: Gravel and charcoal as roughing filtration media - Onyeka Nkwonta; Olufisayo Olufayo; George Ochieng; Josiah Adeyemo; Fred Otieno (South African Journal of Science)
Roughing filtration is an important pre-treatment process for wastewater, because it efficiently separates fine solid particles over prolonged periods, without the addition of chemicals. For this study, a pilot plant was designed at Delmas Coal Mine in the Mpumalanga province of South Africa. The design and sizing of the pilot plant was guided by Wegelin's design criteria. Gravel was used as a control medium because it is one of the most commonly used roughing filter media and because it was used in developing the criteria. We compared the performance of gravel as a filter medium to that of another locally available material, charcoal, for the removal of turbidity in wastewater. The pilot plant was monitored continuously for 90 days from commissioning until the end of the project. The overall performance of the roughing filter in turbidity removal, using gravel or charcoal, was considered efficient for the pre-treatment of waste water. Charcoal performed slightly better than gravel as a filter medium for the removal of turbidity, possibly because charcoal has a slightly higher specific surface area and porosity than gravel, which could enhance sedimentation and other filtration processes, such as adsorption, respectively.